2000
DOI: 10.1108/00070700010348424
|View full text |Cite
|
Sign up to set email alerts
|

Irish consumer preferences for honey: a conjoint approach

Abstract: The ideal honey profile for 153 Irish consumers of honey was one with a thick texture, a dark golden colour, made by a small‐scale producer, at a price of IR£1.95 and packaged in a 454g (1lb) plain glass jar. Least squares regression was used to estimate part worths for the conjoint analysis. Using the scale attribute as a basis for segmentation three distinct segments were identified. Market simulation experiments simulated market shares for 11 products; the ideal products for each segment (three in total), t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
72
2
6

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(88 citation statements)
references
References 11 publications
8
72
2
6
Order By: Relevance
“…The results obtained are similar to those from other studies (28,32). In those studies consumers demonstrated a strong preference for local honey, due to the fact that they were generally sceptical about the quality of imported honey.…”
Section: Results Of Sensory Testsupporting
confidence: 82%
“…The results obtained are similar to those from other studies (28,32). In those studies consumers demonstrated a strong preference for local honey, due to the fact that they were generally sceptical about the quality of imported honey.…”
Section: Results Of Sensory Testsupporting
confidence: 82%
“…Apart from flavour, colour was also very important for participants of the study. In Poland the most preferred honey was dark-gold, as in Ireland (Murphy et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…A study on consumers' preferences in Ireland also found that the price of honey is the most important factor when a decision to purchase is made. According to Murphy et al (2000), consistency, packaging, brand and colour are also important for consumers. Among the Hungarian population it was found that the most important determinants of honey purchase were: quality of product, price, producer and quality of the packaging (Árváné et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Murphy, Cowan, Henchion and O'Reilly (2000) identified three distinct segments in the Irish honey market, each with an "ideal" product. Segment 1 was not price sensitive and preferred honey from small scale producers.…”
Section: Consumer Purchasing Behaviormentioning
confidence: 99%